Back Cover: Aromaticity Reversal in the Lowest Excited Triplet State of Archetypical Möbius Heteroannulenic Systems (Angew. Chem. Int. Ed. 22/2016). Issue 22 (4th May 2016) - Oh, Juwon; Sung, Young Mo; Kim, Woojae; Mori, Shigeki; Osuka, Atsuhiro; Kim, Dongho
Abstract : In analogy to the two faces of the Roman god Janus, the aromaticity of metalated expanded porphyrins that are Möbius aromatic in the ground state can be reversed, as they become Möbius antiaromatic in the lowest excited triplet state. In their Communication onpage 6487 ff., D. Kim, A. Osuka, and co‐workers analyze this reversal of aromaticity by optical spectroscopy and quantum calculations.